2020
DOI: 10.3390/cancers12020302
|View full text |Cite
|
Sign up to set email alerts
|

Low Dosed Curcumin Combined with Visible Light Exposure Inhibits Renal Cell Carcinoma Metastatic Behavior in Vitros

Abstract: Recent documentation shows that a curcumin-induced growth arrest of renal cell carcinoma (RCC) cells can be amplified by visible light. This study was designed to investigate whether this strategy may also contribute to blocking metastatic progression of RCC. Low dosed curcumin (0.2 µg/mL; 0.54 µM) was applied to A498, Caki1, or KTCTL-26 cells for 1 h, followed by exposure to visible light for 5 min (400–550 nm, 5500 lx). Adhesion to human vascular endothelial cells or immobilized collagen was then evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…Unfortunately, its clinical application has been elusive due to its low bioavailability and instability. Recently, however, curcumin coupled with light therapy was observed to improve the compound's bioavailability in skin-related diseases [115]. In bladder cancer cell cultures, Roos et al observed that curcumin treatment followed by light exposure had enhanced antitumor properties, inhibiting cell growth and proliferation [116].…”
Section: Alternative Therapies To Support the Immune System In People With Bladder Cancermentioning
confidence: 99%
“…Unfortunately, its clinical application has been elusive due to its low bioavailability and instability. Recently, however, curcumin coupled with light therapy was observed to improve the compound's bioavailability in skin-related diseases [115]. In bladder cancer cell cultures, Roos et al observed that curcumin treatment followed by light exposure had enhanced antitumor properties, inhibiting cell growth and proliferation [116].…”
Section: Alternative Therapies To Support the Immune System In People With Bladder Cancermentioning
confidence: 99%
“…Interestingly, light irradiation could enhance the biological effects of curcumin. Low-dose curcumin plus visible light exposure could significantly inhibit metastatic processes of renal cell carcinoma [ 267 ], and light exposure might also enhance its efficacy in bladder cancer cell lines [ 268 ]. Exposure to light also enhanced its anti-microbial capacity because of curcumin phototoxicity in bacterial cells [ 269 ].…”
Section: Resultsmentioning
confidence: 99%
“…Light also improves curcumin's bioavailability in skin keratinocytes [22] and renal [23] and bladder cancer cells [24], pointing to a mechanism common to different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…The photodynamic influence on curcumin described here is not restricted to prostate cancer. Light also improves curcumin’s bioavailability in skin keratinocytes [ 22 ] and renal [ 23 ] and bladder cancer cells [ 24 ], pointing to a mechanism common to different cancer types.…”
Section: Discussionmentioning
confidence: 99%